PERILAKU KOMUNIKASI PECANDU GAME ONLINE DI KOTA PANGKALAN KERINCI KABUPATEN PELALAWAN - Sariyanto "; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development of science and technology that is increasingly rapid turns to bring changes in all walks of life. One such human product is the internet. Today's internet technology is growing rapidly, one of its benefits is as a means of entertainment, for example to play. Video game games using an internet connection are known as online games. This study uses a qualitative research method with a qualitative descriptive approach. Qualitative research usually emphasizes participatory observations, in-depth interviews and documentation. So in this study, researchers emphasized observation and in-depth interviews in digging data for the validity of this research, but still using documentation. Thus, this descriptive method is used to systematically describe how the communication behavior of online game addicts. The results of the study show that the use of online games has a huge influence on their communication behavior. These online game addicts are more comfortable using informal languages, which are usually their respective regional languages. This informal language has abbreviations and slang used because online game addicts understand each other the meanings of abbreviations and slang used. The informal language used in communicating is used because according to Paraca this online game addict feels more familiar. Keywords: online game, communication